Pengembangan E-Modul Pembelajaran Instalasi Penerangan Listrik di Sekolah Menengah Kejuruan - Aulia Dara Andermi; Fivia Eliza (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This research is motivated by the application of online learning due to COVID-19, student learning outcomes that have not yet achieved minimal completeness, and the learning process is still centered on teachers due to the unavailability of adequate learning media that students can use for independent study as demanded by the curriculum. 2013 and online learning. This study aims to produce a valid and practical E - Electrical Lighting Installation learning module at SMK Muhammadiyah 1 Padang. This study uses a research and development method with a 4D model. The subjects of this study were students of class XI TITL at SMK Muhammadiyah 1 Padang in the first semester of the 2021/2022 academic year. Based on the results of the study obtained the validity of the media with a valid category. Validation of materials with valid categories. The practicality test with teacher respondents got results in a very practical category and respondents from class XI TITL SMK Muhammadiyah 1 Padang stated that the E - Electrical lighting installation learning module was categorized as very practical. So it can be concluded that the E - Electrical Lighting Installation learning module is valid and can practically be used in the teaching and learning process in schools.